Values of biofeedback in functional constipation - Hussin, Hanim Yati; Yusoff, Azniwani; Mat Hassan, Mohd. Zailani; Ramasamy, Prabhu; Md Nor, Azmi (2010)
Constipation is a debilitating medical condition with a wide range of aetiological factors. The two most common causes include pelvic floor dyssynergia and slow transit constipation. Eventhough constipation is not a life threatening, it does have an adverse effect on patient quality of life and associated with significant morbidity and financial implication. Biofeedback is frequently used as treatment option after conservative management has failed to improve the symptoms.The study aims to analyze the value of biofeedback therapy in the treatment of functional constipation.